KLONING MANFAAT VERSUS MASALAH - Wangko, Sunny; Kristanto, Erwin (UNIVERSITAS SAM RATULANGI, 2010)
Abstract: In general, cloning is an asexual creation of a cell or organism which is genetically identical to its ancestor. Actually, cloning of unicellular and multicellular organisms has been going on in the natural world for thousands of years. Nowadays, in biotechnology, artificial cloning processed by using non-embryonic somatic cells is unbelievably well developed. In medical application, cloning is pointed to therapeutic, reproductive, and replacement usages. However, there are still many controversies, especially if this cloning is related to human beings, law, and ethics norms. Keywords: cloning, cell, organism. Â Â Abstrak: Kloning adalah kreasi secara aseksual dari suatu sel atau organisme yang merupakan salinan genetik dari organisme pendahulu. Secara alamiah kloning telah ditemukan sejak beribu-ribu tahun yang lalu pada organisme unisel sampai ke yang multisel. Dewasa ini kemajuan bioteknologi dalam melakukan kloning artifisial dengan menggunakan sel non embriogenik telah berkembang pesat. Pemanfaatan kloning dalam aplikasi medik ditujukan untuk pengobatan, reproduksi, dan replacement. Walaupun demikian, dalam hal pemanfaatannya masih banyak ketidak sesuaian pendapat, terlebih lagi bila masalah kloning terkait langsung dengan nilai-nilai kemanusiaan, hukum, dan etik. Kata kunci: kloning, sel, organisme.